Why Do Hedge Funds Avoid Disclosure? - TANG, Yuehua (Institutional Knowledge at Singapore Management University, 2013)
We study the “confidential holdings” of hedge funds, where the quarter-end equity holdings are disclosed with a delay through amendments to Form 13F. Funds managing large risky portfolios with nonconventional strategies seek confidentiality more frequently. Stocks in these holdings are disproportionately associated with information-sensitive events or share characteristics indicating greater information asymmetry. Hedge funds trade approximately three times more and take about three times as long to accumulate their confidential stakes compared to their original holdings. Confidential holdings exhibit significantly higher abnormal performance compared to their original holdings, with the annualized outperformance over the 12-month horizon ranges from 5.2% to 7.5%. Together our evidence reveals that private information is the dominant motive for seeking confidentiality and that hedge funds have stock picking skill in their confidential holdings.